The effect of coupling of tectonic compression and overpressure on porosity of deep reservoirs: a case study of southern margin of Junggar Basin, northwest China - Zhang, Fengqi; Gingras, Murray; Shan, Chundi; Lu, Xuesong; Zhuo, Qingong; Zhong, Hongli (Frontiers in Earth Science, 2023)
The majority of high quality clastic reservoirs in the foreland basins, northwest China have anomalously high primary porosity. The intensive tectonic compression, overburden and overpressure importantly impact on the deep reservoir quality in the foreland basins, and that very little research had been so far conducted on this topic. Only considering mechanical compaction without chemical diagenesis, various geological models of tectonic compression, overpressure and porosity were simulated using a comprehensive numerical model. Based on the simulations, the influences of the coupling tectonic compression and overpressure on porosity in deep reservoirs are quantitatively discussed. A case study using a representative well in the thrust belt of the Junggar foreland basin is simulated. The results show that the porosity formed from the early-middle slow burial and late rapid burial type is higher than the almost constant burial type and the early rapid burial and then slow burial type, when the overpressure is formed by the three burial types couple with the same tectonic compression. Importantly, overpressure formed during the early-middle slow burial and late rapid burial type in concert with tectonic compression best preserves high porosity within reservoirs. Either increasing tectonic compression stress early at constant overpressure or increasing the tectonic compression stress at a relative late stage and increasing reservoir overpressure can contribute to porosity loss. The porosity decreases more rapidly in the former case. The later the tectonic compression was applied, the more rapidly porosity of the reservoir decreased. Therefore, late stage tectonic compression accompanied by overpressure has the largest influence on the porosity. The porosity of the Qigu Formation in the well Ds1 in the south margin of Junggar Basin, for example, was decreased by 0.88% in response to intensive tectonic compression in the late Himalayan orogeny. However, porosity formed by overpressure suppression and preservation in the reservoir is 3.66%. So, in addition to vertical compaction and diagenesis, the influence of tectonic compression and overpressure should also be considered in the study of deep reservoir porosity evolution in foreland basin. This study can be helpful for deeply understanding the evolution rule of deep reservoir porosity in foreland basin.